2011
DOI: 10.1166/jnn.2011.4196
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Structure of p-Nitrobenzoic Acid Adlayer on Au(111) Surface in HClO4 Investigated by In-Situ Scanning Tunneling Microscopy

Abstract: The adsorption and adlayer structure of p-nitrobenzoic acid (pNBA) on a Au(111) surface in 0.1 M HCIO4 are investigated by in-situ scanning tunneling microscopy (STM) and cyclic voltammetry. The pNBA adlayer is prepared by dipping Au(111) into a saturated pNBA aqueous solution. The cyclic voltammogram (CV) of the so-prepared Au(111) electrode shows an irreversible cathodic peak at 0.24 V, which corresponds to the electro-reduction reaction from pNBA to hydroxylamine, and a pair of reversible peaks at ca. 0.7 V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…, 17–19 where it specifically adsorbs as p -nitrobenzoate (the PNBA − ion) on the Au(111) surface via the oxygen atoms of carboxylate. 20–22 Similar sharp bands at approximately 3630 cm −1 were observed for other carboxyl-containing adsorbates, such as glycine and fluoroacetate. 23,24 To understand the structural transformation of interfacial water accompanied by the sharp band appearing, three possible structures have been guessed: the formation of an in-plane confined water layer under the ordered adsorption of the PNBA − ions; some non-hydrogen-bonded water OH moieties and isolated water molecules embedded in the adlayer; or water molecules hydrogen-bonded to the adsorbed PNBA − ions.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…, 17–19 where it specifically adsorbs as p -nitrobenzoate (the PNBA − ion) on the Au(111) surface via the oxygen atoms of carboxylate. 20–22 Similar sharp bands at approximately 3630 cm −1 were observed for other carboxyl-containing adsorbates, such as glycine and fluoroacetate. 23,24 To understand the structural transformation of interfacial water accompanied by the sharp band appearing, three possible structures have been guessed: the formation of an in-plane confined water layer under the ordered adsorption of the PNBA − ions; some non-hydrogen-bonded water OH moieties and isolated water molecules embedded in the adlayer; or water molecules hydrogen-bonded to the adsorbed PNBA − ions.…”
Section: Introductionsupporting
confidence: 69%
“…The high-resolution scanning tunneling microscopy (STM) image of PNBA − adsorbed on the Au(111) surface, measured by the Wan group ( Fig. 1b ), 22 showed that the angle between a pair of the elongated blobs was approximately 120° in a (3 × 5) unit cell. To interpret the measured STM image, we compared it with the calculated EC-STM images of three possible Au(111)(3 × 5)–2PNBA − configurations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides continuously improving the measured resolution, a ready alternative strategy is a combination of STM measurements with other surface-sensitive techniques, particularly the vibrational spectroscopies that contain molecular “fingerprints”. For example, an ordered domain of p (3 × 5) was found when p -nitrobenzoic acid (PNAB), which has been widely applied in fuel cells, catalysis, and photodetection, specifically adsorbed on the Au(111) electrodes under the applied electrode potential above 0.44 V vs the standard hydrogen electrode (SHE). , A typical electrochemical STM (EC-STM) image recorded at 0.66 V is depicted in Figure a, which indicates two PNBA molecules adsorbed in the p (3 × 5) supercell. , It is noted that we cannot directly infer any atomistic details from the image because of the blurry resolution. In fact, once the p (3 × 5)-2PNBA configuration was constructed, regardless of the protonation state for the adsorbed PNBA and the configuration for the coadsorbed water molecules, most of the calculated STM images can well reproduce the observed stripes (Figure a).…”
mentioning
confidence: 99%
“…For example, an ordered domain of p(3 × 5) was found when p-nitrobenzoic acid (PNAB), which has been widely applied in fuel cells, catalysis, and photodetection, specifically adsorbed on the Au(111) electrodes under the applied electrode potential above 0.44 V vs the standard hydrogen electrode (SHE). 61,63 A typical electrochemical STM (EC-STM) image recorded at 0.66 V is depicted in Figure 6a, which indicates two PNBA molecules adsorbed in the p(3 × 5) supercell. 61,63 It is noted that we cannot directly infer any atomistic details from the image because of the blurry resolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation